The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10549-017-4305-6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health needs and educational intervention preferences for women with cancer

Abstract: Purpose To assess sexual/vaginal health issues and educational intervention preferences in women with a history of breast or gynecologic cancer. Methods Patients/survivors took a cross-sectional survey at their outpatient visits. Main outcome measures were sexual dysfunction prevalence, type of sexual/vaginal issues, awareness of treatments, and preferred intervention modalities. Descriptive frequencies were performed, and results were dichotomized by age, treatment status, and disease site. Results Of 218… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 47 publications
5
73
1
6
Order By: Relevance
“…In total, 17% of our respondents reported problems with sexuality. The actual proportion of patients with sexuality problems may be higher, as patients may feel uncomfortable reporting these problems [20]. Furthermore, the negative effects of autologous breast reconstruction on arm symptoms, and breast conserving therapy (with additional radiotherapy) on breast symptoms have already been described in the literature [21].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 17% of our respondents reported problems with sexuality. The actual proportion of patients with sexuality problems may be higher, as patients may feel uncomfortable reporting these problems [20]. Furthermore, the negative effects of autologous breast reconstruction on arm symptoms, and breast conserving therapy (with additional radiotherapy) on breast symptoms have already been described in the literature [21].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Da Silva et al, 81% of women stated that it was somewhat-to-extremely important to discuss sexual issues with their provider [18]. Studies with cancer survivors suggest they would like to have conversations on sexuality with their medical team [46]. Additionally, many couples report a desire for candid conversations about sexual health challenges [5,47].…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…A possible explanation for these results may be the age differences and the spontaneous degeneration of sexual desire. Previous publishes studies suggested tamoxifen associated with sexual dysfunction remained controversy in premenopausal patients [35,36]. Mild and partial estrogen effect of tamoxifen actually buffered postmenopausal vaginal dryness and the surveys did demonstrate that sexual desire decreased in patients treated with tamoxifen.…”
Section: Discussionmentioning
confidence: 96%